2011
DOI: 10.1159/000335188
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Expression of Genes Involved in the Endogenous Defense System against Transposons in Cryptorchid Boys with Impaired Mini-Puberty

Abstract: Mini-puberty is the period between 30 and 80 days after birth when testosterone and gonadotropin surges occur in male infants to induce the transformation of gonocytes into adult/dark spermatogonia. Cryptorchid boys with impaired mini-puberty develop infertility despite timely and successful surgical treatment. The decreased germ cell count found in this group of boys could be the result of uncontrolled transposon activity inducing genomic instability and germ cell death. A genome-wide analysis of 18 cryptorch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 66 publications
3
21
0
1
Order By: Relevance
“…It is postulated that sterility is most likely caused by the occurrence of double-strand DNA breaks generated by transposition events [Klattenhoff et al, 2007]. In a previous study, we found impaired expression of DDX4 , MAEL , MOV10L1 , PIWIL2 , PIWIL4 , and TDRD9 genes in boys with cryptorchidism, who exhibited a high infertility risk (HIR) due to altered mini-puberty function [Hadziselimovic et al, 2011a]. That finding indicated that gene instability is induced by impairment in the endogenous system that defends against transposons; we hypothesized that this instability may contribute to the development of azoospermia.…”
mentioning
confidence: 76%
“…It is postulated that sterility is most likely caused by the occurrence of double-strand DNA breaks generated by transposition events [Klattenhoff et al, 2007]. In a previous study, we found impaired expression of DDX4 , MAEL , MOV10L1 , PIWIL2 , PIWIL4 , and TDRD9 genes in boys with cryptorchidism, who exhibited a high infertility risk (HIR) due to altered mini-puberty function [Hadziselimovic et al, 2011a]. That finding indicated that gene instability is induced by impairment in the endogenous system that defends against transposons; we hypothesized that this instability may contribute to the development of azoospermia.…”
mentioning
confidence: 76%
“…Thus, on the basis of the reviewed evidence, it can be proposed that piRNAs play much broader roles than it have been previously appreciated. A study by Hadziselimovic et al (2011) reported the lack of expression of MOV10L1 in cryptorchid boys at high risk of developing azoospermia. The lower level of testosterone and free-androgen was observed in cryptorchid infants, indicating insufficient gonadotropin and testosterone stimulation (Pierik et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of MOV10L1 has been documented in patients at risk of azoospermia. In the group of cryptorchid boys at high risk of infertility, the expression of DDX4, MAEL, MOV10L1, PIWIL2, PIWIL4, and TDRD9 was impaired, which indicated that gene instability induced by impaired expression of transposon silencing genes contribute to the development of azoospermia (Hadziselimovic et al 2011). The MOV10L1 gene is thus named because it is homologous to MOV10.…”
Section: Role Of Mov10l1mentioning
confidence: 99%
“…This suggests that gene instability induced by impaired expression of transposon-silencing genes may have contributed to the development of azoospermia. Intact mini-puberty appeared to be essential for the development of the endogenous defense system mediated by transposon silencing [25]. …”
Section: Role Of Temperaturementioning
confidence: 99%